2005
DOI: 10.1016/j.molcel.2005.05.010
|View full text |Cite
|
Sign up to set email alerts
|

The Tumor Suppressor RASSF1A and MAP-1 Link Death Receptor Signaling to Bax Conformational Change and Cell Death

Abstract: Tumor cells typically resist programmed cell death (apoptosis) induced by death receptors. Activated death receptors evoke Bax conformational change, cytochrome c release, and cell death. We report that the tumor suppressor gene RASSF1A is required for death receptor-induced Bax conformational change and apoptosis. TNFalpha or TRAIL stimulation induced recruitment of RASSF1A and MAP-1 to receptor complexes and promoted complex formation between RASSF1A and the BH3-like protein MAP-1. Normally, MAP-1 is inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
211
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(226 citation statements)
references
References 36 publications
12
211
1
2
Order By: Relevance
“…MOAP-1 can associate with both wild type and the dMT mutant of RASSF1A in a time-dependent manner as previously observed (data now shown and Baksh et al, 2005). Similarly, RASSF1A self association was preserved in the dMT mutant of RASSF1A in a similar way to wild-type self association ( Figure 4a).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…MOAP-1 can associate with both wild type and the dMT mutant of RASSF1A in a time-dependent manner as previously observed (data now shown and Baksh et al, 2005). Similarly, RASSF1A self association was preserved in the dMT mutant of RASSF1A in a similar way to wild-type self association ( Figure 4a).…”
Section: Resultssupporting
confidence: 86%
“…Detailed five-amino acid deletions revealed that the sequences 131 SQAEI and 300 ELHNFL were required for microtubule localization ( Figure 1b). It is interesting that 131 SQAEI is the ataxia telangeictasia mutated (ATM) phosphorylation site on RASSF1A (Agathanggelou et al, 2001) and 300 ELHNFL is just downstream of the site of association with the only known downstream effector of RASSF1A-mediated cell death, the modulator of apoptosis 1 (MOAP-1 at amino acid 311 REEEEHL) (Baksh et al, 2005;Foley et al, 2008). These results are similar to some of the published observations, which suggest that both N-and C-terminal regions of RASSF1A determine microtubule localization.…”
Section: Resultssupporting
confidence: 78%
“…This suggests a functional interaction between Bax and the CsAsensitive permeability transition pore complex (PTPC) (Marzo et al, 1998b;Belzacq et al, 2003). Another protein outside of the PTPC that may be required for Bax-mediated MOMP is the so-called modulator of apoptosis 1 (MAP-1) (Baksh et al, 2005;Tan et al, 2005).…”
Section: Mitochondrial Membrane Permeabilization: the Central Event Omentioning
confidence: 99%
“…Given that RASSF1A has a tumor suppressor function by inhibiting cell proliferation and survival (Dammann et al, 2000;Shivakumar et al, 2002;Song et al, 2004;Baksh et al, 2005), we thus examined whether Skp2 inhibits the tumor suppression function of RASSF1A. Overexpression of wild-type and S203A mutant forms of RASSF1A resulted in a significant loss of viability in U2OS cells (Figures 6a and b).…”
Section: Skp2 Regulates the Antiproliferative And Antisurvival Functimentioning
confidence: 99%
“…Furthermore, RASSF1A induces a G 1 arrest by engaging the Rb family G 1 -S checkpoint through inhibition of cyclin D1 (Shivakumar et al, 2002). RASSF1A is also involved in apoptosis by linking death receptor signaling to the apoptotic machinery (Baksh et al, 2005;Oh et al, 2006;Matallanas et al, 2007). However, the precise mechanism by which RASSF1A is regulated remains unclear.…”
Section: Introductionmentioning
confidence: 99%